AL-QUR’AN DI LAYAR DIGITAL: ANTARA KEMUDAHAN AKSES DAN HILANGNYA SAKRALITAS - sore, mukhlis (Jurnal Studi Islam, 2025)
This research discusses the influence of digital technology on the accessibility and sacredness of the Quran. The traditional approach of reading and studying the Quran, through printed manuscripts and hands-on learning, has shifted to digital platforms such as apps and websites. This eases access, allowing users to read, listen to and interpret the Quran anytime and anywhere. This study aims to analyse the benefits and challenges of accessing the Quran digitally while maintaining appropriate respect and ethics. It uses Lev Manovich's new media theory to discuss the implications of digital formats on the experience and perception of sacred texts among Muslims. Findings show that digital access increases learning opportunities, but can also reduce the deep spiritual connection usually felt through the physical Quran. Users must navigate how to maintain the sacredness of the Quran amidst the conveniences offered by technology. Key words: Quran, Digital, Accessibility, Sacred